Nano-scale Heat Transfer in Nanostructures Toward Understanding and Engineering Thermal Transport ​ - Al-Ghalith, Jihong (SpringerBriefs in Thermal Engineering and Applied Science,, 2018)
The book introduces modern atomistic techniques for predicting heat transfer in nanostructures and discusses the applications of these techniques on three modern topics. The study of heat transport in screw-dislocated nanowires with low thermal conductivities in their bulk form, which represent the knowledge base needed for engineering thermal transport in advanced thermoelectric and electronic materials and suggests new routes to lower thermal conductivity that could promote thermoelectricity. The study of high-temperature coating composite materials, which facilitates the understanding of the role played by composition and structural characterization, a problem difficult to approach by experiments. And the understanding of that the impact of deformations, such as bending and collapsing on thermal transport along carbon nanotubes, is important as carbon nanotubes, due to their exceptional thermal and mechanical properties, are excellent materials candidates in a variety of applications, including thermal interface materials, thermal switches and composite materials. Presents atomistic numerical methods for nanoscale heat transfer from both scientific and engineering perspectives; Reviews the most recent important literature in a clear presentation by world-class professionals; Serves as an exceptional resource for students interested in modern heat transfer topics.